THE DEVELOPING MATHEMATICS MODULE OF SOCIAL ARITHMETIC BY USING SCIENTIFIC APPROACH FOR STUDENT OF GRADE VII - Tri Erry Austya; Sumargiyani Sumargiyani (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Limited teaching materials are one of the problems that affect the achievement of learning objectives. Teaching materials that can help the student to learn independently is a module. This research is development research that aims to produce Mathematics Module of Social Arithmetic by using a Scientific Approach for Student of Grade VII SMP/ MTs ( Junior High School) and to know the module quality that developed and worthy of use in Mathematics learning. This research uses Research and Development developed by identifying the potential and problem, collect the information, designing the product, validation of product design, revise product design, product trial stage, and revise the product. The subject in this research and development of the module are material experts, media experts, and students. The Mathematics Module, using the scientific approach, is developed based on five learning steps: observing, questioning, collecting information, reasoning, and communicating. This product has been through the revision step based on the suggestion and feedback from media experts, material experts, and student's responses to the module. The result of the research shows that the Mathematics Module of Social Arithmetic, using the Scientific Approach for Student of Grade VII SMP/ MTs (Junior High School), has good quality from criteria of validity. Based on the assessment from material experts obtained an average score of 96,67, which fulfills the criteria very good. From media, experts obtained average score 69, which fulfills the criteria well, and the student's response showed that the quality of the module is excellent, with an average score of 86,29. Based on the research, the Mathematics Module of Social Arithmetic using the Scientific Approach for Student VII Grade of SMP/ MTs( Junior High School) is worthy of use in Mathematics Learning.